2018
DOI: 10.4028/www.scientific.net/ddf.382.297
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Peat as a Potential Low-Cost Adsorbent Material for COD and NH<sub>3</sub>-N Removal

Abstract: Micro-peat (M-P) was demonstrated in the present study as a potential low cost natural adsorbent for the removal of COD and ammoniacal nitrogen (NH3-N) from landfill leachate. A series of batch experiments were carried out under fixed conditions and the influence of mixture ratio was investigated. The characteristics of leachate were then determined. Results indicated that leachate is non-biodegradable with high concentration of COD (2739.06 mg/L), NH3-N (1765.34 mg/L) and BOD5/COD ratio (0.09). The optimum ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Initial investigation revealed that the leachate has high concentration of color, COD, and ammoniacal nitrogen (NH 3 -N), with lower value of BOD 5 :COD ratio (<0.1). Hence, Simpang Renggam landfill can be categorized as stabilized landfill leachate [4,25]. Stabilized landfill leachate is known to contain refractory organic compound [3,23].…”
Section: Characteristics Of Leachatementioning
confidence: 99%
See 2 more Smart Citations
“…Initial investigation revealed that the leachate has high concentration of color, COD, and ammoniacal nitrogen (NH 3 -N), with lower value of BOD 5 :COD ratio (<0.1). Hence, Simpang Renggam landfill can be categorized as stabilized landfill leachate [4,25]. Stabilized landfill leachate is known to contain refractory organic compound [3,23].…”
Section: Characteristics Of Leachatementioning
confidence: 99%
“…This is believed to occur due to the removal efficiency of COD. The removal of color was observed to decrease with further increment of AC which attained the maximum removal rate of both parameters and therefore the increase of available sorption sites may result in aggregation which can decrease the probability of molecules contacting all available adsorption sites [4,25].…”
Section: Media MIX Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced oxidation approach are economically expensive and can have problems of chlorine oxidation. Other types of treatments such as ozonation [1][2][3], coagulationflocculation [4] also have been used in investigations but have economic cost. Generally, many methods have been applied for the treatment of wastewater and adsorption remained the most preferred because of the ease in operation as well as its global application.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural waste biomass is currently a topic of interest that has been receiving considerable attention in the past few decades [12]. In recent years, different native and low-cost materials, such as peat soil, feldspar, cockle shell (CS), seaweed, rice husk, wood sawdust, banana frond, and limestone, have been considered successful alternatives for wastewater treatment [13]. Several operational parameters, such as pH, dosage, and shaking speed, mainly influence the minimization of chemical oxygen demand (COD) and ammonia nitrogen (NH 3 -N).…”
Section: Introductionmentioning
confidence: 99%